Artisanal Gold Mine Management Based on Ecological Justice in the Peulumat Mountains, South Aceh - Suganda, Delfi; Mahmuddin, Mahmuddin; Huda, Muhammad Chairul; Ma’mun, Sukron (Universitas Negeri Semarang, 2024)
Aceh represents one of the autonomous regions situated on the western frontier of Sumatra Island within the unitary structure of the Republic of Indonesia. Despite the abundance of natural resources in Aceh, a substantial portion still needs to be adequately managed systematically and in a contemporary manner. Among these resources are artisanal gold mines, where extraction processes rely on manual labor and limited tools. One such mining site is located in the Peulumat Mountains. The operation of this mine suffers from a dearth of technical expertise, primarily managed manually by the local community. However, the utilization of these natural resources should not be managed by entities that neglect ecological justice, which is crucial for fostering the sustainability of nature itself. This research investigates how laborers at the artisanal gold mine in Mount Peulumat navigate their operations to achieve ecological justice. This qualitative research employed a socio-legal approach and was conducted in the rural community of Gampong Gunong Rotan. This study finds a patron-client relationship in the management and allocation of mining proceeds. Two pivotal elements influencing the realization of ecological justice within the mining locale emerged: natural phenomena and a belief in divine principles. Locals perceive certain natural occurrences, such as the flooding of the mining wells, as an indication to cease gold extraction promptly. Furthermore, a prevailing belief dictates that extracted gold should not be solely for personal gain but shared with those in need, reflecting a commitment to divine values.